Singapore Airlines responding to the Middle East Behemoths on the Kangaroo Route - FAN, Terence Ping Ching (Institutional Knowledge at Singapore Management University, 2024)
Set in 2015, this case study is about how Singapore Airlines (SIA) and the Middle Eastern behemoths — Emirates, Qatar Airways, and Etihad Airways — adopt differentiation strategies to compete in the full-service passenger air travel industry. It highlights the multifaceted nature of an airline’s differentiation strategies, noting that various levels of differentiation correspond to different pricing tiers. Each airline offers a range of products such as cabins or ‘classes’, enabling them to vary their degree of differentiation across their offerings. The case identifies factors that the airlines can leverage to enhance their competitiveness and those that are immutable. In addition, this case includes detailed pricing and product information that students can use to distil important insights for strategic analysis. Since the 2000s, Emirates and other Middle Eastern airlines have undergone substantial growth over the years, creating challenges for their competitors, especially along the Kangaroo Route (a popular air travel route that connects the continents of Europe and Australasia). Consequently, Australia-based Qantas opted for a strategic shift and “threw in the towel”, replacing its traditional Sydney-Melbourne-Singapore-London flights with a new route through Sydney-Melbourne-Dubai-London. This change allowed Qantas to integrate with Emirates’ network, streamlining connectivity. On the other hand, SIA competed head-to-head with Emirates. Due to its highly differentiated products and services, SIA commanded a price premium over Emirates. However, Emirates offered more flight connection choices than SIA, translating to a higher demand for air travel. To remain competitive, what strategy should SIA adopt? Should SIA match its airfare pricing with Emirates to attract more passengers? Students will be able to gain insights into the strategic positioning of SIA and Emirates in terms of their products and services. They will learn to explain the airlines’ competitive dynamics and product differentiation strategies, as well as assess if SIA should align its pricing with Emirates.